PENGEMBANGAN VIDEO PEMBELAJARAN SOLIDWORKS DI PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNIVERSITAS SEBELAS MARET - Rizki Rohmat Nur Alim Isnaini; Yuyun Estriyanto; Taufik Wisnu Saputra (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
Mechanical Engineering Education Program FKIP UNS is a study program that produces professional staff in the teaching and engineering fields who have competence in carrying out teaching processes, workshops, manufacturing processes, manufacturing drawing designs, etc. One of the courses in MEEP is Computer Aided Design 2. This course is a compulsory subject that must be taken by MEEP students in semester 4. The problem that occurs in this research is the implementation of learning in Computer Aided Design 2 courses at MEEP is not maximized, so the problem is not known the level of suitability between the implementation of the learning program with the semester learning design and the resulting output. Therefore, appropriate learning videos are needed in the learning process for CAD 2 courses. The feasibility testing of this learning video involves 3 parties, there are subjects experts, media experts, and users. From the assessment of material experts, it was obtained that the percentage of eligibility averaged 92.28% and was included in the "very feasible" category. From the assessment of media experts, it was obtained that the average percentage of eligibility was 88% and was included in the "very feasible" category. The trial process was attended by MEEP students who were taking CAD 2 courses. From the user response data of 70 respondents, it was obtained that the average eligibility percentage was 84.34% and was included in the "very feasible" category. The conclusion is that the development of learning videos in Computer Aided Design 2 courses is very feasible and suitable for use in the learning process.